DABAM: an open‐source database of X‐ray mirrors metrology. (1st May 2016) - Sanchez del Rio, Manuel; Bianchi, Davide; Cocco, Daniele; Glass, Mark; Idir, Mourad; Metz, Jim; Raimondi, Lorenzo; Rebuffi, Luca; Reininger, Ruben; Shi, Xianbo; Siewert, Frank; Spielmann-Jaeggi, Sibylle; et al.
Abstract : DABAM, an open‐source database of X‐ray mirrors metrology to be used with ray‐tracing and wave‐propagation codes for simulating the effect of the surface errors on the performance of a synchrotron radiation beamline. Abstract : An open‐source database containing metrology data for X‐ray mirrors is presented. It makes available metrology data (mirror heights and slopes profiles) that can be used with simulation tools for calculating the effects of optical surface errors in the performances of an optical instrument, such as a synchrotron beamline. A typical case is the degradation of the intensity profile at the focal position in a beamline due to mirror surface errors. This database for metrology (DABAM) aims to provide to the users of simulation tools the data of real mirrors. The data included in the database are described in this paper, with details of how the mirror parameters are stored. An accompanying software is provided to allow simple access and processing of these data, calculate the most usual statistical parameters, and also include the option of creating input files for most used simulation codes. Some optics simulations are presented and discussed to illustrate the real use of the profiles from the database.